Distributional impact of globalization-induced migration: Evidence from a Nigerian village - Steve Onyeiwu; Raluca Iorgulescu Polimeni; John M. Polimeni (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
One of the contentious issues about the globalization process is the mechanism by which globalization affects poverty and inequality. This paper explores one of the various strands of the globalization–inequality–poverty nexus. Using microlevel survey data from over 300 poor households in the small village of Umuluwe (about 30 miles west of the regional capital of Owerri) in Southeast Nigeria, the paper investigates whether individuals who migrate from the village to take advantage of the urban-biased globalization process do better than non-migrant villagers. The paper concludes that while the migrant villagers tend to earn slightly higher incomes than the non-migrant villagers, the poverty profiles of both categories of households are essentially the same. In other words, and contrary to conventional wisdom, globalization has not succeeded in alleviating poverty amongst the poor villagers who explicitly took advantage of the process. The paper argues that, by changing relative prices in the urban areas, structural adjustment appears to have eliminated any advantage that globalization may have bequeathed to the migrant villagers. – migration ; Nigeria ; poverty ; prices
Keywords: O15; R23; J31; 330; Internationale Wanderung; Armut; Nigeria